Analisa Kepatuhan Minum Obat Anti Tuberculosis: Perbandingan Penggunaan Layanan Pesan Singkat dengan Pengawas Minum Obat - Maulan Agung Nugroho; Kumboyono Kumboyono; Setyoadi Setyoadi (Jurnal Akademika Baiturrahim Jambi, 2023)
The Directly Observed Treatment Short-course (DOTS) strategy is the best strategy recommendation for pulmonary tuberculosis (TB) intervention at the international level and has been implemented in Indonesia. However, the bored may also occur among Medication Supervisor (PMO) resulted medication non-adherence to the TB patients. This study aims to determine differences in the level of patient medication adherence through the use of Short Message Service (SMS) with PMO at Puskesmas Dinoyo, Malang. The post-test only control group design was used on a population of pulmonary TB patients who were registered at the Puskemas Dinoyo Malang during July to December 2012 with a total of 33 patients. The sample were recruited using simple random sampling. The Self Reported Questionnaire and observation form used as study instrument. Fisher exact test was used in hypothesis testing. The results showed non- significant difference between the drug adherence among respondents who received SMS and respondents who received reminders from PMO only (p-value 0.50 > 0.05). Providing reminders at the same time every day, either by SMS or PMO only, is equally beneficial in the success of treatment. Together will increase compliance and reduce the negligence to take medication. Longitudinal design is recommended for further study.